2006
DOI: 10.1002/esp.1317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gully erosion rates through interviews and measurements: a case study from northern Ethiopia

Abstract: Gullying has been widespread in the Ethiopian Highlands during the 20th century. It threatens the soil resource, lowers crop yields in intergully areas through enhanced drainage and desiccation, and aggravates flooding and reservoir siltation. Knowing the age and rates of gully development during the last few decades will help explain the reasons for current land degradation.In the absence of historical written or photographic documentation, the AGERTIM method (Assessment of Gully Erosion Rates Through Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 23 publications
5
151
1
2
Order By: Relevance
“…between 2·3 and 7·4 t ha −1 y −1 (Nyssen et al, 2006c). At present, average area-specific short-term gully erosion rates are 1·1 t ha −1 y −1 .…”
Section: Gully Erosionmentioning
confidence: 87%
See 2 more Smart Citations
“…between 2·3 and 7·4 t ha −1 y −1 (Nyssen et al, 2006c). At present, average area-specific short-term gully erosion rates are 1·1 t ha −1 y −1 .…”
Section: Gully Erosionmentioning
confidence: 87%
“…Monitoring of gully erosion rates in the study area during three years revealed an increase of gully volume from 22 805 to 23 877 m 3 , corresponding to a specific gully erosion rate of 4·1 t ha −1 y −1 (Nyssen et al, 2006c).…”
Section: Gully Erosionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been an endemic ecological problem of growing concern not only in the humid tropics but in many parts of the world and the literature is replete with numerous studies (Moyensons, 2003;Martinez-Cassanova et al, 2003;Martinez, 2003;Poesen et al, 2003;Valentin et al, 2005;Sirvio et al, 2004;Ronken and Bennett, 2006;Nyssen et al, 2006;Marzolff et al, 2009;Cassali et al, 2009;Poesen, 2011) Many published studies also exist on the mode of occurrence, mapping and assessment and modeling of this phenomenon in an urban environment, particularly in southeastern Nigeria (Udosen, 1998;, 2000;, 2004;, 2006;, 2008, Udosen andEssiett, 2012 ;Akpokodje et al, 2010;Essien and Okon, 2011;Essien and Essen, 2012;Nwilo et al 2011;Ehiorobo and Izinyin 2012;Jonathan and Joshua, 2013;Abdulfatai et al, 2014 amongst others). It is clear from these studies that urban expansion in most parts of Nigeria (as in other countries) leads to increase in impervious surfaces, reduces infiltration rates and consequently increased surface runoff/reduction in concentration time leading to incision and development of gullies.…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, considerando que a produção de células se origina no perímetro do caule, a árvore aumenta o diâmetro "de fora para dentro", o que se chama de crescimento secundário das plantas (COSTA, 2001 NYSSEN et al, 2006;POESEN et al, 2003). Recentemente, encontram-se na literatura estudos que descrevem a dendrogeomorfologia como um método alternativo com potencial para analisar a erosão em voçorocas (BODOQUE et al, 2011b;CORONA et al, 2011;MALIK, 2008;VANDEKERCKHOVE et al, 2001).…”
Section: Anatomia Do Lenho Das áRvoresunclassified